Varieties of the state of exchange of nitrogenous metabolites (creatinine, urea, uric acid and bilirubin) and their immune accompaniment at rats - Kuchma, Igor; Flyunt, Igor-Severyn; Ruzhylo, Sofiya; Zukow, Walery; Bilas, Volodymyra; Popovych, Igor (Journal of Education, Health and Sport, 2021)
Background. Earlier we found that even in intact rats, certain parameters of nitrogenous metabolism and immunity fluctuate in a fairly wide range, which further expands in cases of prolonged water loads. The links between the individual parameters of metabolism and immunity were revealed. Based on this, the aim of this study was to create groups that are homogeneous in the parameters of nitrogenous metabolism, followed by a search for the characteristic parameters of immunity. Material and methods. Experiment was performed on 60 healthy female Wistar rats, both intact and loaded with different mineral waters. The plasma levels and urinary excretion of the nitrogenous metabolites (creatinine, urea, uric acid and bilirubin) were determined. Immune status was assessed by thymocytogram, splenocytogram, blood leukocytogram and immunocytogram, as well as by phagocytosis parameters of blood neutrophils and monocytes. Results. The characteristic features of the members of the most numerous (29 animals) of the first cluster are moderately elevated plasma urea and upper borderline creatinineemia in combination with lower borderline uricemia. In members of the third cluster (22 animals), all seven parameters are in the range of normal. In contrast, rats of the second cluster (n=9) were found to have significantly increased levels of urea and creatinine excretion, as well as uricemia. Each cluster is accompanied by a specific constellation of immune parameters. The overall accuracy of the classification is 95%. Conclusion. The variety of states of exchange of nitrogenous metabolites is accompanied by specific constellations of immune parameters.